2015
DOI: 10.1287/mnsc.2014.2084
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Field Price Discretion: Empirical Evidence from Auto Lending

Abstract: I n many markets, it is common for headquarters to create a price list but grant local salespeople discretion to negotiate prices for individual transactions. How much (if any) pricing discretion headquarters should grant is a topic of debate within many firms. We investigate this issue using a unique data set from an indirect lender with local pricing discretion. We estimate that the local sales force adjusted prices in a way that improved profits by approximately 11% on average. A counterfactual analysis sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(47 citation statements)
references
References 44 publications
2
45
0
Order By: Relevance
“…They find that while the effect of store traffic on sales exhibits diminishing returns, having more in-store labor can alleviate this effect. Appendix Table A4) Notable works include those by Anderson and Xie (2012), Subramanian and Subramanyam (2012), Li et al (2014), and Phillips et al (2015). In general, the problems examined in this literature relate to the factors that affect pricing decisions and how different pricing schemes affect revenues.…”
Section: Services Management and Retailing (Onlinementioning
confidence: 99%
See 1 more Smart Citation
“…They find that while the effect of store traffic on sales exhibits diminishing returns, having more in-store labor can alleviate this effect. Appendix Table A4) Notable works include those by Anderson and Xie (2012), Subramanian and Subramanyam (2012), Li et al (2014), and Phillips et al (2015). In general, the problems examined in this literature relate to the factors that affect pricing decisions and how different pricing schemes affect revenues.…”
Section: Services Management and Retailing (Onlinementioning
confidence: 99%
“…In general, the problems examined in this literature relate to the factors that affect pricing decisions and how different pricing schemes affect revenues. For example, Phillips et al (2015) investigate the effect of centralized versus decentralized pricing strategies on firm performance. They note the potential endogeneity of price and consumer response, and address this using a control function approach in their model.…”
Section: Services Management and Retailing (Onlinementioning
confidence: 99%
“…We defined and measured the instrumental variables of the competition for each category of restaurant and the entire market. Similar to Phillips et al (2015), we calculated the average of the discount rates that had been offered recently. When the platform firms and merchants set the discount rate, historical discount rates may affect their decisions.…”
Section: Predictors and Instrumentsmentioning
confidence: 99%
“…The selection of banks from Asia-Pacific countries is based on the finding of Elzinga andMills (2011), andFu, Lin, andMolyneux (2014), who conducted an empirical study on bank competition and financial stability in 14 Asia-Pacific countries and found that banks in this region are able to obtain greater discretion in terms of derivatives' price-setting. Good price discretion boosts the profitability of banks and reduces their insolvency risk, in addition to increasing banking concentration (product differentiation) (Homburg, Jensen, & Hahn, 2012;Phillips, Simsek, & van Ryzin, 2015). This situation illustrates that pricing power boosts the capacity in Asia-Pacific banks that serve as "capital buffers."…”
Section: Introductionmentioning
confidence: 99%